2016
DOI: 10.1016/j.jhevol.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of subsistence changes on humeral bilateral asymmetry in Terminal Pleistocene and Holocene Europe

Abstract: Analyses of upper limb bone bilateral asymmetry can shed light on manipulative behavior, sexual division of labor, and the effects of economic transitions on skeletal morphology. We compared the maximum (absolute) and directional asymmetry in humeral length, articular breadth, and cross-sectional diaphyseal geometry (CSG) in a large (n > 1200) European sample distributed among 11 archaeological periods from the Early Upper Paleolithic through the 20(th) century. Asymmetry in length and articular breadth is rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 89 publications
4
77
0
Order By: Relevance
“…The lack of clear distinctions in the type of tools used is a constraining factor in interpretation of our data and therefore, we use generalized levels of activity to interpret the results. Another factor increasing variability in upper limb bone structure is bilateral asymmetry in behavioral use, which also varies between populations (Auerbach and Ruff, ; Sládek et al, ). Because of sampling limitations (due to poor preservation, pathological cases or missing elements, see Supporting Information Table S1), we included both right and left upper limb elements in this study, which likely also increased variation, although we found no significant difference between right and left sides.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of clear distinctions in the type of tools used is a constraining factor in interpretation of our data and therefore, we use generalized levels of activity to interpret the results. Another factor increasing variability in upper limb bone structure is bilateral asymmetry in behavioral use, which also varies between populations (Auerbach and Ruff, ; Sládek et al, ). Because of sampling limitations (due to poor preservation, pathological cases or missing elements, see Supporting Information Table S1), we included both right and left upper limb elements in this study, which likely also increased variation, although we found no significant difference between right and left sides.…”
Section: Discussionmentioning
confidence: 99%
“…Averaging is further not likely to bias analysis, because lower limb dimensions have limited asymmetry (Auerbach & Ruff, 2006). Given the potential for asymmetric loading due to handedness, left and right humeral diaphyseal products and circumference were analyzed separately, though comparisons of average values are also reported (Auerbach & Ruff, 2006; Sládek et al, 2016). Results from average values agreed with patterns seen in left and right elements.…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that in men diaphyseal dimensions and vertical head diameter are more asymmetric, while in women the humeral length is more asymmetric. Despite differences between the two studies, the laterality pattern could be associated with different activity patterns related to the different manipulative behaviors of the sexes (Sládek et al, 2007(Sládek et al, , 2016. In this work, we have observed through 3DGM that the female mean shape presents higher laterality differences than in males.…”
Section: Discussionmentioning
confidence: 57%
“…Considering all of this, the dominant hand is associated with a larger size and greater development of MSMs in the corresponding arm. The dominance of the right arm has been observed in different osteological populations of Homo sapiens, including recent hunter-gatherers, medieval British and Slovenes, the Romano-British population, German Neolithic farmers, Central European Late Eneolithic peoples, and Early Bronze Age and Northern European Mesolithic peoples (Schultz, 1937;Thould and Thould, 1983;Constandse-Westermann and Newell, 1989;Reichel et al, 1990;Trinkaus et al, 1994;Steele and Mays, 1995;Churchill and Formicola, 1997;Wilczak, 1998;Mays, 1999;Cuk et al, 2001;Lazenby, 2002;Auerbach and Ruff, 2006;Sládek et al, 2007Sládek et al, , 2016Weiss, 2009;Blackburn, 2011).…”
Section: Introductionmentioning
confidence: 99%